Gender Affirmative Care Clinic: An Overview - Sanjay Sharma; Bela Sharma (Indian Journal of Plastic Surgery)
Transgender healthcare is an evolving multispecialty field including medical and social domains catering to the needs of a specific subset of population presenting with gender incongruence, differences in sexual development/orientation, requiring care rather than cure. Delivery of transgender healthcare is done through gender friendly healthcare facilities, which are designated as “gender affirmative care clinics (GACC).” The primary purpose of the gender affirmative care clinic is to be the “one stop solution” for a person seeking affirmative care. The main objective is to facilitate care with compassion and prevent/mitigate dysphoria. The components of the GACC should include reception cum front office; affirmative mental healthcare department; affirmative medical, surgical, and sexual healthcare department; diagnostics, legal, and ethics department, as well as inpatient care. The GACC should be preferably located in a place that is easily accessible to the community members and has an “open plan.”